1985
DOI: 10.1115/1.3239701
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling From Two Rows of Holes Inclined in the Streamwise and Spanwise Directions

Abstract: This paper describes the results of an experimental investigation into the film cooling effectiveness of two rows of holes inclined in the stream and spanwise directions. The effects of hole and row spacings and combinations of inclinations are investigated in the presence of free-stream pressure gradients and turbulence for a typical range of blowing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 2 publications
5
24
0
Order By: Relevance
“…They also found that the jets from the downstream row extended further from the wall and penetrated deeper into the mainstream than their first row because the jets from the second row were diverted less by the approaching flow due to the greater momentum deficit of the approaching flow at the second row. Jubran and Brown [17] suggested that effectiveness downstream of a second row of jets was dependent on the state of the development of the film from the first row, and its development length increased with increasing row spacing, which subsequently resulted in a near two-dimensionality when the downstream row was encountered.…”
Section: Introductionmentioning
confidence: 98%
“…They also found that the jets from the downstream row extended further from the wall and penetrated deeper into the mainstream than their first row because the jets from the second row were diverted less by the approaching flow due to the greater momentum deficit of the approaching flow at the second row. Jubran and Brown [17] suggested that effectiveness downstream of a second row of jets was dependent on the state of the development of the film from the first row, and its development length increased with increasing row spacing, which subsequently resulted in a near two-dimensionality when the downstream row was encountered.…”
Section: Introductionmentioning
confidence: 98%
“…They documented (1) skewing of the velocity towards the downstream edge of the hole exit and (2) flow disturbances created by the jet-crossflow interaction upstream of the hole exit and within the jet supply. Inclined jets were studied by Launder and York (1974), Kadotani and Goldstein (1979), Yoshida and Goldstein (1984), and Jubran and Brown (1985). Lee et al (1992) presented three-dimensional mean velocity and vorticity distributions, accompanied by flow visualization, for 35O-inclined streamwise injection with m = 5 0 and freestream turbulence intensity (FSTl) of 0.2%.…”
mentioning
confidence: 99%
“…The works of Goldstein et al [2], Foster and Lempard [3], and Jubran and Brown [4] to name a few, are representative of this type of work. Data specific to turbine film cooling problems were reported by Mehendale and Han [5], who investigated the effects of mainstream turbulence on the film cooling effectiveness and heat transfer coefficient for a turbine airfoil leading edge.…”
Section: Imentioning
confidence: 98%